Real‐time whole‐plant dynamics of heavy metal transport in Arabidopsis halleri and Arabidopsis thaliana by gamma‐ray imaging - Kaisa Kajala; Katherine L. Walker; Gregory S. Mitchell; Ute Krämer; Simon R. Cherry; Siobhan M. Brady (Plant Direct, 2019)
Abstract Heavy metals such as zinc are essential for plant growth, but toxic at high concentrations. Despite our knowledge of the molecular mechanisms of heavy metal uptake by plants, experimentally addressing the real‐time whole‐plant dynamics of heavy metal uptake and partitioning has remained a challenge. To overcome this, we applied a high sensitivity gamma‐ray imaging system to image uptake and transport of radioactive 65Zn in whole‐plant assays of Arabidopsis thaliana and the Zn hyperaccumulator Arabidopsis halleri. We show that our system can be used to quantitatively image and measure uptake and root‐to‐shoot translocation dynamics of zinc in real time. In the metal hyperaccumulator Arabidopsis halleri, 65Zn uptake and transport from its growth media to the shoot occurs rapidly and on time scales similar to those reported in rice. In transgenic A. halleri plants in which expression of the zinc transporter gene HMA4 is suppressed by RNAi, 65Zn uptake is completely abolished.